Avaliação ultrassonográfica da artéria carótida comum em equinos da raça Quarto de Milha - Aguiar, Adriana Cristina Saldanha de [UNESP] (2015)
Common carotid artery in horses trifurcates with some anatomical variations and it is the main supply of arterial blood to the brain. It is known that carotid occlusion can cause encephalic lesions in rats and humans. There are few studies on this vessel, including ultrasonografic evaluation of his vessel in this species. This study evaluated the common carotid artery in 50 American Quarter horses with different ages, separated into three groups (group I: >2years, n=14; group II: 3-10 years, n=21; group III 15-30 years, n=15), and reference values for intima-media thickness (IMT), resistivity index (RI), pulsatility index (PI) and diameter were obtained for both arteries. Exam was performed using an 18 MHz transducer on jugular groove, on level of C5-C6. Mean left diameter was 8.71 ± 1.09 mm for group I; 10.11 ± 0.72 mm for group II and 10.72 ± 0.96 mm for group III. Right diameter was 8.92 ± 1.24 mm for group I; 10.96 ± 1.06 mm for group II and 11.76 ± 1.07 mm for group III. IMT was 0.90 ± 0.15 mm; 1.02 ± 0.09 mm and 0.97 ± 0.10 mm for groups I, II and III, respectively. Mean RI and PI obtained were 0.75 ± 0.07 and 1.63 ± 0.33 for group I; 0.81 ± 0.06 and 2.08 ± 0.46 for group II; 0.90 ± 0.10 and 3.20 ± 0.74 for group III, respectively. The variables RI, PI and IMT are not influenced by gender or side, but were by age. Diameter was influenced by both, age and side, and right diameter was always greater than the left